Identification of Heterobasidion annosum (Fr.) Bref s. l. pestholes in Altai Krai by the methods of DNA-analysis - D. N. Shuvaev (Сибирский лесной журнал, 2016)
In this work was tested method of DNA-diagnostic for identification and further localization of pest holes of Heterobasidion annosum (Fr.) Bref s.l. Heterobasidion annosum is dangerous enemy for coniferous trees because they have no effective natural resistance against this pathogen. Therefore it can easily spread in stand and be the cause of its death. The most aggressive and rate of spreading of pathogen require appropriate events foridentifying and mapping of infectious holes. Identification of H. annosum by fruit bodies is usually difficult because of the rarity of their formation. Furthermore, this method cannot allow determination of the hidden infectious borders in the dying stand. For example, in the clone bank of Pinus sylvestris from Ozersky forestry during long time attempts todeterminecauses of trees’ death were unsuccessful because fruit bodies weren’t found there and the experiments for induction of fruit bodies also yielded nothing. We have applied the method of DNA-analysis and identified that the cause of trees’ death was H. annosum. The rapidity and accuracy are advantages of DNA-diagnosiswhile the conventional methods are time-consuming. However, DNA-markers aren’t a panacea without a complete description of the stand infected by pathogen and the events aimed against it. This is a preliminary study where we wanted to demonstrate applicability of the method and began the first stage for further detail localization of pestholes.